Pengaruh Kompetensi Kepala Sekolah terhadap Kinerja Guru (Studi Deskrifsi Analitik pada SD Negeri di Wilayah Kabupaten Pangandaran) - Sobirin Sobirin (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2022)
The ideal view of the professionalism of school principals is reflected in the image of future principals, namely principals who have expertise, responsibility, and a sense of fellowship supported by strong professional ethics. Some school supervisor notesin Cijulang sub-district are more principals whose competence is still below the standard. Therefore, this research takes the title: